2021
DOI: 10.3390/cancers13164099
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sentinel Lymph Node Metastasis in Postoperatively Upgraded Invasive Breast Carcinoma Patients

Abstract: Sentinel lymph node (SLN) biopsy (SLNB) usually need not be simultaneously performed with breast-conserving surgery (BCS) for patients diagnosed with ductal carcinoma in situ (DCIS) by preoperative core needle biopsy (CNB), but must be performed once there is invasive carcinoma (IC) found postoperatively. This study aimed to investigate the factors contributing to SLN metastasis in underestimated IC patients with an initial diagnosis of DCIS by CNB. We retrospectively reviewed 1240 consecutive cases of DCIS by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…22,23 In previous investigations, the LVI positivity was reported as pointing to a high risk of SLN metastasis. [24][25][26][27] Theoretically, the process that results in nodal metastasis begins with lymphangiogenesis followed by LVI. If LVI accompanying a lesion is detected, LN metastasis should always be suspected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 In previous investigations, the LVI positivity was reported as pointing to a high risk of SLN metastasis. [24][25][26][27] Theoretically, the process that results in nodal metastasis begins with lymphangiogenesis followed by LVI. If LVI accompanying a lesion is detected, LN metastasis should always be suspected.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a significant positive correlation was found between LVI and SLN metastasis, which is consistent with the literature data. [24][25][26][27] Preoperative breast MRI is clinically important because of its high sensitivity in evaluating breast lesions. 28,29 It is frequently used today.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that several clinical characteristics of cancer patients are associated with LNM, such as age, thickness of the primary tumor, tumor differentiation, and T stage 15–19 . Combining these factors with CT/MRI characteristics would be a potential way to improve the accuracy of predicting LNM.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with DCIS, a meta-analysis of 16 studies reported an SLN metastasis rate of 4.9% (153 of 3153). Subsequent large studies have reported rates between 1.9% (23 of 1240) and 7.6% (49 of 649), through 4.4% (127 of 2892) in the largest of such studies. Therefore, SLN metastasis rate in patients with preoperative diagnosis of DCIS is much lower compared with the 13.7% SLN metastasis rate in the SLNB arm of the SOUND trial.…”
mentioning
confidence: 97%